2015
DOI: 10.1038/ncomms8221
|View full text |Cite|
|
Sign up to set email alerts
|

Facile synthesis of ultrahigh-surface-area hollow carbon nanospheres for enhanced adsorption and energy storage

Abstract: Exceptionally large surface area and well-defined nanostructure are both critical in the field of nanoporous carbons for challenging energy and environmental issues. The pursuit of ultrahigh surface area while maintaining definite nanostructure remains a formidable challenge because extensive creation of pores will undoubtedly give rise to the damage of nanostructures, especially below 100 nm. Here we report that high surface area of up to 3,022 m2 g−1 can be achieved for hollow carbon nanospheres with an oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
337
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(343 citation statements)
references
References 64 publications
5
337
0
1
Order By: Relevance
“…This is an innovative approach to developing a new energy technology, which directly converts mechanical energy into electrochemical energy without energy being wasted on the outer circuitry and decreases energy conversion loss. Importantly, the development of both high performance energy storage devices [208][209][210][211][212][213][214] and the materials [215][216][217][218][219][220][221][222] used in the devices is essential for the fabrication of highly effective hybridized "all-in-one energy harvesting and storage devices" in the future.…”
Section: Simple Connection Of Energy Harvester and Storage Devicementioning
confidence: 99%
“…This is an innovative approach to developing a new energy technology, which directly converts mechanical energy into electrochemical energy without energy being wasted on the outer circuitry and decreases energy conversion loss. Importantly, the development of both high performance energy storage devices [208][209][210][211][212][213][214] and the materials [215][216][217][218][219][220][221][222] used in the devices is essential for the fabrication of highly effective hybridized "all-in-one energy harvesting and storage devices" in the future.…”
Section: Simple Connection Of Energy Harvester and Storage Devicementioning
confidence: 99%
“…All the samples delivered an outstanding electrochemical performance, which can be ascribed to high specific surface area, hollow structure, nitrogen functionalization, and shell architecture. In addition, hollow carbon nanospheres with exceptionally ultrahigh surface area and well-defined nanostructure were reported by Xu et al [45] After activation, the carbon nanospheres had a large surface area of 3022 m 2 g −1 and an outer diameter of 69 nm. All cyclic voltammetry (CV) curves exhibited rectangular shapes and the galvanostatic charge-discharge curves displayed typical triangular profiles, implying a typical EDLC behavior.…”
Section: Carbon Hollow Nanostructurementioning
confidence: 81%
“…Conjugated polymer hollow spheres were synthesized via soft template approach reported in the literature [30]. FTIR spectrum indicated that aniline and pyrrole were co-polymerized in soft templates (see Supplementary Figure S1).…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
“…Hence, the kinetics can be analyzed qualitatively using the difference of the potential peaks where sluggish kinetics will need more voltage or time to reach the peak current or the current where depletion of ions at the surface commences [49]. This indicates significant catalytic behavior [50,51] of the GHCSA aerogel for Fe(CN)6 4− /Fe(CN)6 3− redox couple, which may be attributed to doping of nitrogen atoms derived from conjugated polymer precursors [30] into microporous shells of carbon spheres within aerogel matrix (See Figure S12).…”
Section: Thermoelectric Cellsmentioning
confidence: 99%